Application Model Learning Team Games Tournament on Students' Mathematics Learning Results - Agnes Lugfi Wulandari mtk; Paraniah Paraniah; Subhanudin Subhanudin; A Rasul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the success of increasing the application of the team games tournament (TGT) learning model to mathematics learning outcomes in grade VIII students of YKK Ebenhaezer Mimika Papua Junior High School. This research included the type of Classroom Action Research with the research subjects of grade VIII A students at SMP YPK Ebenhaezer Mimika Papua totaling 29 students. The research design used the Kemmis and Mc. Taggart model. The results showed that mathematics learning outcomes in grade VIII A students at SMP YPK Ebenhaezer could be improved using the team games tournament (TGT) learning model. After the first cycle of actions, students who met the KKM 18 students 62 percent and did not meet the KKM 11 students 38 percent. After the second cycle of action, 22 students met the KKM 76 percent and did not meet the KKM 7 students 24 percent. The results of teacher activity in cycle I were 66 percent and in cycle II there was an increase to 77 percent. As for the results of student activity in cycle I, which was 70 percent and in cycle II there was an increase to 76 percent.